Evaluation of platelet concentrates prepared from whole blood donations with collection times between 12 and 15 min: The BEST Collaborative study - de Korte, Dirk; Bontekoe, Ido J; Fitzpatrick, Áine; Marks, Denese; Wood, Ben; Gravemann, Ute; Bohoněk, Miloš; Kutner, Jose M (Vox sanguinis, 2022)
BACKGROUND AND OBJECTIVES: In many countries, whole blood (WB) donations with collection times between 12 and 15 min are not allowed to be used for platelet concentrates (PC). Since the development of guidelines, many process-related changes have been introduced. We aimed to determine the effect of WB with long collection times on PC quality. MATERIALS AND METHODS: Five participating centres tested buffy coat (BC)-derived PC in platelet additive solution type E prepared from only WB collections lasting <12 min (control) versus similar PC including one BC from a collection lasting >12 min (study group, n = 8). One centre produced platelet-rich plasma (PRP)-derived PC from single donations (<10 or >12 min). All PC were stored at 22 ± 2°C and sampled on Days 1, 6 and 8 post-collection for in vitro quality determination. RESULTS: Average collection time was significantly longer in the study group compared to controls (8.9 ± 2.6 vs. 7.3 ± 1.3 min, p < 0.001). There were no differences in volume, platelet concentration, basal CD62P expression, soluble-CD62P and CCL5 levels, or nucleotide content between the groups. Stimulation with TRAP-6 resulted in comparable levels of cell surface CD62P. On Day 8, all PC fulfilled requirements for pH. The findings from single PRP-derived PC centre were similar. CONCLUSION: PC with one BC and single PRP derived from collections lasting >12 min had equivalent in vitro quality to controls during storage. This study provides evidence that 12-15 min donations should not be excluded for PC preparation and justifies to readdress the guidelines to <15 min instead of <12 min of collection in line with current practice in some countries.
Keywords: Blood Platelets; trombocyty; Blood Donors; Humans; plazma bohatá na destičky; lidé; Blood Preservation; Platelet-Rich Plasma; dárci krve; konzervace krve